Relasi Agama dan Budaya Menurut Durkheim Sebagai Peran PAK Dewasa dalam Mengkonstruksi Pemahaman Jemaat Terhadap Tradisi Mengongkal Holi - Sinaga, Rut Yesika; Rantung, Djoys Anneke; Naibaho, Lamhot (Jurnal Teologi Cultivation, 2023)
Culture is a legacy of ancestors that continues to develop, but the integration of religion and culture often causes debate in a society. The Mangongkal Holi ritual of the Toba Batak tribe in North Sumatra is the subject of research in relation to the perspective of Christianity. This research aims to use Durkheim's view of the relationship between religion and culture as a tool to analyze Mangongkal Holi. In addition, the researcher offers the role of Adult Christian Religious Education as a solution regarding the integration of religion and culture in this tradition. The research shows how moral solidarity in Christianity affects the understanding and practice of the Mangongkal Holi tradition. In addition, Adult Christian Religious Education is proposed as an educational method to strengthen the community's understanding of the relationship between religion and this cultural tradition. This approach emphasizes self-direction and the desire for continuous learning as important elements in understanding the integration of religion and culture.